Trading In Influence Dalam Kasus Kuota Import Daging Sapi Yang Melibatkan Partai Politik Anggota Legislatif Eksekutif Serta Swasta - Syauket , Amalia; Nisa, Putri Ginatun (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2025)
Trading in influence is a type of corruption that involves individuals who hold power or authority to influence policy decisions within the legislative or executive branches. This practice is often carried out by those who have direct access to policymakers. Until now, trading in influence has not been explicitly regulated in Indonesia’s Anti-Corruption Law. This academic study, which prioritizes secondary data, aims to examine how the offense of trading in influence applies in the Beef Import Quota case, which involved a political party chairman, members of the legislature, and party cadres. The study seeks to answer: under which legal provision were they prosecuted? And why? The results of this research lead to the conclusion that a patronage scheme with a horizontal trading influence pattern was used in the corruption case surrounding beef import procurement at the Ministry of Agriculture of the Republic of Indonesia in 2013–2014. The case involved a political party president acting as the patron-subject, a party cadre serving as the Minister of Agriculture, and an intermediary (also a party cadre), targeting the object of influence — PT Indoguna. This case was prosecuted under bribery charges, as it was proven that PT Indoguna paid IDR 40 billion. The charges were based on the similarity of the acts to bribery, especially because they involved abuse of power and the perpetrators were public officials.